Teacher Creativity in Learning in the New Normal Time SDN 3 Bulusan Karangdowo Klaten - Bambang Sumardjoko; Murfiah Dewi Wulandari; Putra Pamungkas (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to describe the planning of Teacher Creativity in Learning in the New Normal at SDN 3 Bulusan, to describe the implementation of Teacher Creativity in Learning in the New Normal at SDN 3 Bulusan, to describe the evaluation of Teacher Creativity in Learning in the New Normal at SDN 3 Bulusan. The method used in this research is to use a qualitative research approach design. The type of research used in this descriptive qualitative research is the place of research at SDN 3 Bulusan Karangdowo with the object of research being teachers and students, the research subject is learning in the classroom with data sources from interviews, documents, and observations. The results of the research are teacher creativity in the use of online learning media at SDN Bulusan, classroom and subject teachers adjust learning media with material that will be delivered to students to achieve learning objectives. The teacher's creativity in using learning methods at SDN 3 Bulusan is that the teacher can use the question and answer method to make learning interesting and not boring, so that students take an active role in online learning. The obstacle faced by teachers at SDN 3 Bulusan lies in its implementation which makes online learning less effective and efficient. 4. The obstacle faced by teachers at SDN 3 Bulusan lies in its implementation which makes online learning less effective and efficient.